STUDY OF EFFICACY AND TOXICITY OF HYPOFRACTIONATED THORACIC RADIOTHERAPY 17 GRAY IN 2 FRACTIONS FOR PALLIATION IN ADVANCED NON-SMALL-CELL LUNG CANCER: Palliation in Advanced Non-Small-Cell Lung Cancer - Arif, Maj Salman; Rasul, Shahid Rasul; Haider, Naeem; Mahmood, Ahsan; Syed, Abdus Samad; Nadeem, Mohammad; Amin, Zulfiqar (Pakistan Armed Forces Medical Journal, 2012)
Objectives: To determine the efficacy and toxicity of hypofractionated thoracic radiotherapy 17 Gray (Gy) in 2 fractions for palliation in advanced non.small-cell lung carcinoma.Study design: A quasi-experimental study.Place and duration of study: Oncology department, Combined Military Hospital, Rawalpindi, from 4th July 2008 to 4th Nov 2009.Material and Methods: Fifty four patients with histologically and/or cytologically confirmed unresectable stages III and IV non small cell lung cancer, with performance status 2 or 3 and expected survival . 2 months were treated with megavoltage radiation therapy 17 Gy in 2 fractions one week apart, with symptoms due to intrathoracic disease (cough, dyspnea and hemoptysis) and toxicity due to radiation therapy (dysphagia secondary to esophagitis) assessed as per common toxicity criteria adverse event version 3.0 on day 0 before treatment and day 30 after start of treatment.Results: Grades of cough, hemoptysis and dyspnea showed significant improvement after treatment (p